Heraclitus and Thales' conceptual scheme : a historical study - Finkelberg, Aryeh. (Jerusalem Studies in Religion and Culture, 2017)
In Heraclitus and Thales' Conceptual Scheme: A Historical Study Aryeh Finkelberg offers an alternative to the traditional teleological interpretation of early Greek thought. Instead of explaining it as targeted at later results, viz. philosophy, as this thought was first conceptualized by Aristotle and has been regarded ever since, the author seeks to determine its intended meaning by restoring it to its historical context as evinced, inter alia, by epigraphic and papyrological evidence, in particular the Gold Leaves, the Olbian bone plates, and the Derveni papyrus. This approach, together with a considerable amount of hitherto unidentified or largely disregarded evidence, yields a picture of early Greek thought significantly different from the traditional history of 'Presocratic philosophy'.